Determination of Awareness Towards Olympic Concepts of National Athletes Who Students in Dücze University Sport Sciences Faculty - Mensur Pehlivan; Ömer Sivrikaya (Selcuk University, 2022)
The aim of this study was to determine the awareness towards olympic concepts of national athletes who students in Dücze University Sport Sciences Faculty. The research is a descriptive research and phenomenological design has been used. In the research, the method of "easily accessible situation sampling" was preferred. The study group of the research consists of nine national athletes from different branches studying at Düzce University in the 2015-2016 academic year. The data were collected using the interview technique. In the research, 11 questions were asked to the participants in order to measure their awareness of the Olympic concepts. The coding process was carried out by examining the data summarized and interpreted in the descriptive analysis in more detail. After the data was encoded, similar data were brought together and themed. As a result, It was observed that the knowledge level of national athletes participating in the study about the Olympics was not at the level expected from elite athletes. In addition to the elite performance training given to national athletes, it has become clear that training to raise awareness about the Olympics has emerged.